Pesantren Literature: Products and Creators of Literatcy Culture in Indonesia Education - Joko Widodo (International Journal of Educational Narratives, 2023)
Background. Pesantren literature is a literary product written by pesantren people or about the phenomenon of pesantren life. Purpose. This study aims to see the implementation of the independent curriculum on the principles of the Strengthening the Profile of Pancasila Students (P5) Project through pesantren literary writing. Method. The learning method used is critical cooperative with the aim of improving aspects of critical thinking skills. This type of research is qualitative with a case study approach. This research was conducted at SMA Al Maahira IIBS Malang. This research involved students as students. Each student in a small group has a pesantren literary writing project. Results. The pesantren literature written is based on the values of pesantrenan that they have learned. The results showed that there was a process of internalizing the value of pesantren to students. The results of the internalization are explored to be used as a source of ideas. The results showed that there are ethical and political implications in learning pesantren literary writing. The aspect of ethical implications shows that pesantren literature has benefits in developing students' critical thinking skills. In the political aspect, pesantren literature is a cultural product as well as the creator of pesantren literacy culture in Indonesia. Conclusion. Thus, Indonesian education has great potential in utilizing the phenomenon of pesantrenan or the like to be applied in the independent curriculum. The pesantren literary writing project with a critical cooperative method contains speaking, reading, and writing skills.